Quarter Life Crisis and Self-Awareness of Biology Education Students at Universitas Riau in Completing their Final Assignment - Nadila Husnah; LN Firdaus LN Firdaus; Riki Apriyandi Putra (Journal of Education and Learning Research, 2025)
The student's final assignment is proof of the success of the process of achieving academic achievement. However, in the completion process, students often experience various obstacles both from within and outside themselves. These obstacles cause students to experience Quarter Life Crisis (QLC). Self-awareness can help them understand themselves completely, both in terms of nature, character and emotions so they are able to face QLC. This research aims to find out how much influence self-awareness has on QLC experienced by Biology Education students at FKIP (Faculty of Education and Teacher Traning), Universitas Riau. To achieve this goal, descriptive research was carried out using a survey method. The results of the research show that the self-awareness and QLC level of Biology Education students at FKIP Universitas Riau are both classified as medium. The level of self-awareness has a negative effect. These findings indicate that efforts are still needed to increase self-awareness of Biology Education students at FKIP Universitas Riau. This can be achieved by getting students into the habit of carrying out regular self-evaluations so that they can find out their strengths and weaknesses. If these efforts are achieved, students' QLC levels are expected to decrease.